Domestic Violence against women: Review of theories, prevalence and its effective factors - Hasanpoor Azghadi, batool; simbar, masoomeh; kermani, mahdi (Advances in Nursing & Midwifery, 2012)
Abstract Background and aim Violence against women is a human rights issue, but it is also a health issue and its physical, mental and social consequences can put women, family and society’s health in danger. This article aims to review domestic violence phenomenon with a psychological and social approach and estimates its prevalence.